Trans-anethole, the major constituent of the essential oil of anise, improves the antiarthritic effects of methotrexate in rats (Research, Society and Development, 2022)
The aim of this study was to evaluate the effect of trans-anethole in combination with methotrexate, compared to monotherapy with trans-anethole or methotrexate, on inflammatory parameters and oxidative stress of arthritic rats. The experimental model of arthritis induced by Freund's complete adjuvant (AIA) in rats was used. Treatment with trans-anethole and methotrexate, in combination or monotherapy, was started on the day of AIA induction and continued for 21 days. The association of anethole (62.5 mg/Kg) to methotrexate (6 mg/Kg) therapy was able to further reduce both the oxidative stress induced by arthritis and the inflammatory events that characterize the disease, as demonstrated by the following indicators: 1) decrease in the edema of the hind legs, in the score of secondary lesions, in the recruitment of leukocytes to the articular cavity and in the plasma myeloperoxidase activity; 2) increase in plasma content of reduced thiols and total antioxidant capacity; 3) diminution of protein carbonylation in plasma, liver and kidneys; 4) decrease in lipid peroxidation in the liver; 5) reduction in the hepatic ROS content; 6) enhancement of the activity of the antioxidant enzymes and GSH/GSSG ratio. In general, the combination anethole + methotrexate presented a substantially higher effect than the monotherapy with anethole or methotrexate (at the same doses). The data obtained in this work allow us to conclude that the use of trans-anethole in combination with methotrexate suppressed arthritic progression in rats, with the main advantage of reduction of methotrexate dose, attenuating adverse effects caused by high dose therapy.